2021
DOI: 10.1101/2021.05.28.21258027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria treatment-seeking behaviour and its associated factors: A cross-sectional study in rural East Nusa Tenggara Province, Indonesia

Abstract: Introduction. The World Health Organization recommends seeking medical treatment within 24 hours after transmission of malaria to reduce the risk of severe complications and its onwards spread. However, in some parts of Indonesia, including East Nusa Tenggara Province (ENTP), this adherence is not achieved for a range of reasons including delays in visiting health centres. This study aims to determine factors related to the poor understanding of appropriate malaria treatment–seeking behaviour (AMTSB) of rural … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Chukwuocha, Okpanma, Nwakwuo, and Dozie (2014) found that age, marital status, educational status of murder and family socioeconomic status add determinants of delay in care-seeking behaviour of children under five suffering from malaria. Guntur, Kingsley, and Islam (2021) found that low level of education, Low economic status, distance to health facilities and occupation were determinants of delay in seeking care for Malaria in Indonesia.…”
Section: Introductionmentioning
confidence: 97%
“…Chukwuocha, Okpanma, Nwakwuo, and Dozie (2014) found that age, marital status, educational status of murder and family socioeconomic status add determinants of delay in care-seeking behaviour of children under five suffering from malaria. Guntur, Kingsley, and Islam (2021) found that low level of education, Low economic status, distance to health facilities and occupation were determinants of delay in seeking care for Malaria in Indonesia.…”
Section: Introductionmentioning
confidence: 97%